A phenomenological analysis of subterranean operations in the Israel Defense Forces. Issue 4 (4th July 2021) - Ben Shalom, Uzi; Gold, Niv; Berger, Corinne; Stern, Nehemia; Antonovsky, Avishai; Peleg, Dvir
ABSTRACT: This article analyses the experiences of IDF soldiers involved in subterranean operations in Gaza. While tunnel warfare is a central element in warfare, few sociological studies have focused on this element of combat. In-depth interviews reveal the day-to-day experiences of the specialised combat engineering units tasked with subterranean operations during the past two decades. The themes identified are: 'Operational activity in tunnels as an experience', 'Courage and danger', 'Selection and classification of manpower' and 'Accumulating experience'. An awareness for generational differences in the narratives allows an analytical model based on four different models for organising forces for operations in tunnels.